Virtual (music) exhibits as critical spaces of community engagement: The diversitycapebreton.ca web portal - Ostashewski, Marcia; Favaro, Eric; Rosenblum, Ely; Nalepa, Patricia; Zoric, Jana; Vukobratovic, Jelka (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2015)
A great many Central and Eastern Europeans were among the laborers who immigrated to work in Cape Breton mines and steel mills in the 19th and early 20th centuries. Despite their continuing contribution to the region, Cape Bretoners of Eastern and Central European descent have been overshadowed in public memory and scholarship by the island’s more familiar Scottish and Acadian communities. This article addresses a project through which an international and interdisciplinary group of scholars living locally in Cape Breton and abroad, as well as numerous local community partners, aimed address this lacuna. The participants’ concrete objective was the production of a web portal – diversitycapebreton.ca – that opens up onto reams of curated digital material. These digital media complement the project’s program of public outreach. This article focuses on ways in which this digital curation project served (and continues to serve) as a space for the continual collaborative re-creation of communities and histories.